2011
DOI: 10.1371/journal.pone.0018726
|View full text |Cite
|
Sign up to set email alerts
|

CD4 Dynamics over a 15 Year-Period among HIV Controllers Enrolled in the ANRS French Observatory

Abstract: BackgroundThere are few large published studies of HIV controllers with long-term undetectable viral load (VL). We describe the characteristics and outcomes of 81 French HIV controllers.Methods and ResultsHIV controllers were defined as asymptomatic, antiretroviral-naïve persons infected ≥10 years previously, with HIV-RNA <400 copies/mL in >90% of plasma samples. All available CD4 and VL values were collected at enrolment. Mixed-effect linear models were used to analyze CD4 cell count slopes since diagnosis. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 30 publications
7
62
1
1
Order By: Relevance
“…This response, in turn, readily controls the infection, maintaining a steady state between infected cells and the immune system (Fig. 5A), which may result in residual systemic activation and mild progression in the absence of therapy (45)(46)(47). The virtuous circle between the virus and the host response would be interrupted when the frequency of latently infected CD4 ϩ T cells falls to a very low level, hindering the stochastic reactivation of fit viruses (18) and leading to fewer viral amplification events.…”
Section: Discussionmentioning
confidence: 99%
“…This response, in turn, readily controls the infection, maintaining a steady state between infected cells and the immune system (Fig. 5A), which may result in residual systemic activation and mild progression in the absence of therapy (45)(46)(47). The virtuous circle between the virus and the host response would be interrupted when the frequency of latently infected CD4 ϩ T cells falls to a very low level, hindering the stochastic reactivation of fit viruses (18) and leading to fewer viral amplification events.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether a proportion of elite controllers are persistently <1 copy/mL or if all elite controllers have detectable virus by single-copy assay at some point during the course of untreated HIV infection. Interestingly, a French study showed that elite controllers with transient low-level viremia, termed "blips", do not experience CD4 declines compared to those who do not have detectable viremia [21]. In contrast to elite controllers, LTNP are typically viremic by standard clinical viral load assays.…”
Section: Elite Controllers and Ltnp As Models For Functional Cure Of mentioning
confidence: 99%
“…They can maintain a viral load below the detection threshold of standard assays (Ͻ50 copies HIV RNA/ml plasma) for decades and show a very low risk of progression to AIDS (4,23). Converging evidence indicates that HIV controllers have developed particularly efficient cellular antiviral responses, which can maintain an active control of the infected target cell population in the long term.…”
mentioning
confidence: 99%